Short communication. Forage and nutritive value of the pruning residues (leaves plus summer lateral shoots) of four grapevine (Vitis vinifera L.) cultivars at grape harvest and two post-harvest dates - Kok, D.=700 1 Ates, E.; Korkutal, I.; Bahar, E.
Es, En)
Ilus., 19 ref.
Keywords: PIENSOS; CONTENIDO MINERAL; VALOR NUTRITIVO; RESIDUOS DE COSECHAS; PODA; VITIS VINIFERA; PRODUCCION; ESPAÑA